SEARCH OF VARIABILITY OF THE COMPANION OF THE CLASSICAL CEPHEID EV SCT - Egorova, I. A.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2017)
Spectroscopic observations of EV Sct obtained on 4m telescope at KPNO showed that the secondary component is probably situated within the instability strip (Kovtyukh & Andrievsky, 1999). Some observers (Pel, 1976; Mermilliod, 1987) have noted a signicant data scattering on the light curve. Therefore the companion of EV Sct perhaps is a small amplitude variable star. We present results of photoelectric observations of the EV Sct.